Intact animacy perception during chase detection in ASD - Vanmarcke, Steven (Sci Rep, 2017)
We explored the strength of implicit social inferences in adolescents with and without Autism Spectrum Disorder (ASD) using a chasing paradigm in which participants judged the absence/presence of a chase within a display of four seemingly randomly moving dots. While two of these dots always moved randomly, the two others could fulfill the role of being either the chasing (wolf) or chased (sheep) dot. In the chase-present (but not the chase-absent) trials the wolf displayed chasing behavior defined by the degree to which the dot reliably moved towards the sheep (chasing subtlety). Previous research indicated that chasing subtlety strongly influenced chase detection in typically developing (TD) adults. We intended to replicate and extend this finding to adolescents with and without ASD, while also adding either a social or a non-social cue to the displays. Our results confirmed the importance of chasing subtlety and indicated that adding social, but not non-social, information further improved chase detection performance. Interestingly, the performance of adolescents with ASD was less dependent on chasing subtlety than that of their TD counterparts. Nonetheless, adolescents with and without ASD did not differ in their use of the added social (or non-social) cue.